Tipografia: Ideograma Ocidental - Borges, Priscila Monteiro (2005)
Taking typography as the construction of fonts and the arrangement of letters on any support, this work pretends to show that digital typography has changed the iconic characteristic of written alphabetic languages. The principal iconic trace of ideograms and the way Chinese written signify are shown in order to explain the iconic aspects of written alphabetic languages. Different digital typography are examined through the semiotic theory of Peirce to show that digital age has expanded the visual language of written alphabetic languages making it get similar to ideogramatic system. This comparison may show how the iconicicity of written alphabetic language works in the digital age. Besides Peirce´s semiotic, the studies done by Haroldo de Campos about ideograms, which he used in his concrete poems, are fundamental for this work. The concept of hybridism made by Canclini is used to show how the visual and the verbal languages are intersected. A little bit of written history is shown with Roger Chartier, Foucault and Geoffrey Sampson. Pierre Lévy and Manual Castells are references to explain how digital age works. Questions about the motivation and the arbitrariness of the words are also discussed, because the written alphabet seems to have increased the distance between word and image, creating a conventional and mostly arbitrary verbal language. The pos-modern world tends subtract language, messages have to be understood in a short time and probably this has increased the iconicity of written language because the icon is the most simple sign. In this situation, typography has grown its iconic side. The text is not considered any more as a sequence of letters that have meaning, but also, as a picture that have important imagetic information. Understanding the process of iconicity in written language may show where present communication is going. We could conclude that the flexibility of digital language creates a new perspective for typography. Digital fonts emphasizes the iconicity of written language in many degrees. There are even fonts that don`t use the current alphabet in favor of pictures, creating a very specific text. The digital typography has provided new forms of language hybridism. Letter and image seems to have a new relation in the written language.